ETHICAL ASSESSMENT MANAGER AGAINST A CONFLICT OF INTEREST THE CORPORATE SOCIAL INTEREST THE CORPORATE SOCIAL - Inova Fitri Siregar (Akuntansi dan Teknologi Informasi, 2018)
The idea of social responsibility or known as Corporate Social Responbility ( CSR) is getting widely accepted.Group that supports discourse social responsibility of the opinion that the company cannot be separated from individuals who involved in this, namely the owner and employees.But they should not just think of profit f, but also must have sensitivity and concern for public.With the csr activity conducted by the company manager, and has budgeted by the a company so create conflicts of interest.The purpose of this research is to analyze how assessment ethical manager to conflict an interest in the activity of their Sample used is all employers who engaging in activities corporate social responsibility as many as 30 companies located in pematang pudu sub district mandau.The result that has been achieved are the judgments ethical manager to a conflict of interest has been included in four criteria: from the benefits , justice , fulfilling the right and maintenance , but each company should have alternative how minimize pressure from the public so that not avoid activity CSR